A substantial rise in competence for all health and social services in the municipality. : Municipal health managers’ experiences with a nurse-staffed emergency department. - Hovland, Gro; Halding , Anne-Grethe; Kyrkjebø, Dagrun; Kleiven, Ole Tormod; Zakariassen, Erik; Ytrehus, Siri (Nordisk Tidsskrift for Helseforskning, 2023)
The Norwegian Directorate for Health has initiated the “Pilot emergency department” project, which is a new model for emergency services in remote areas that are struggling to secure acute medical expertise. In satellite urgent care centres, nurses carry out consultations by way of video conferencing with physicians. This study explores the participating managers’ experiences. Ten managers from five municipalities participated in qualitative interviews, supplemented with qualitative content analysis. The potential for an improvement in the expertise and recruitment of new nurses motivated the managers to participate. They viewed the project as a means to address the need to improve acute care expertise in the health and social care sector as a whole. The managers emphasised supporting the nurses for the new combined role as “satellite nurse” and regular nursing duties in the municipality. Novel forms of interdisciplinary collaboration were judged as essential for improving expertise. The managers’ impression was that the nurses found their new duties interesting, with the potential for increasing recruitment and stabilising the nursing workforce.
Keywords: competence; nurse-staffed emergency room; manager; qualitative; interview